Sharp size-selective catalysis in a liquid solution over Pd nanoparticles encapsulated in hollow silicalite-1 zeolite crystals. Issue 92 (20th September 2016) - Wei, Fang-Fang; Liu, Jian; Zhang, Qiu-Yun; Zhang, Yu-Tao; Zhang, Xing; Cao, Chang-Yan; Song, Wei-Guo
Abstract : Pd nanoparticles encapsulated in a hollow silicalite-1 zeolite with sharp size-selective catalysis in solution was designed by a lab-in-a-shell method. Abstract : A lab-in-a-shell method was designed to prepare Pd nanoparticles encapsulated in hollow silicalite-1 zeolite crystals for size-selective catalysis in liquid solution. Due to the pore size limitation of the microporous silicalite-1 shell (0.53 × 0.56 nm), the catalyst showed high activity in the hydrogenation of 3-methyl-2-butenal (0.38 × 0.62 nm) and cinnamaldehyde (0.54 × 0.92 nm), but no activity for 3, 3-diphenylacrylaldehyde (0.81 × 1.0 nm).